Tarakan Smart City: Meningkatkan Transparansi dan Akuntabilitas Layanan Publik melalui E-Government - Margareta; Putri, Anastasia Vienessa; Maskut, Deby Naya; Kwuta, Rosdiana Meni; Sipayung, Baren (Tumoutou Social Science Journal, 2025)
This study examines the utilization of e-government to enhance transparency and accountability in public services in Indonesia. The main issue addressed is the lack of transparency and accountability in the delivery of public services, which can hinder the realization of good governance and erode public trust. The aim of this research is to analyze how e-government can be implemented to improve transparency and accountability in public services, as well as to identify the challenges and strategies in its implementation. The research method used is a literature review, analyzing various relevant sources such as academic journals, research reports, and policy documents. The findings of the study indicate that e-government has the potential to enhance transparency and accountability in public services through the provision of publicly accessible and transparent information, empowering the public in overseeing the use of public funds, and improving the efficiency and effectiveness of bureaucracy. However, the implementation of e-government also faces challenges, such as the digital divide, data security issues, and a lack of digital literacy. This study recommends that the government improve digital infrastructure, strengthen data security systems, enhance public digital literacy, and develop integrated and user-friendly e-government applications and platforms. The concept of "Tarakan Smart City" presented in this study offers a comprehensive and integrated smart city development model by incorporating e-government into various aspects of urban life.